Effect of Air Profiling and Frother Concentration on a Flotation Bank Performance - Maldonado-Saavedra, M (Oficyna Wydawnicza Politechniki Wroclawskiej, 2023)
The impact of air distribution on the metallurgical performance of a flotation bank operating with a mineral slurry having a moderate and high frother concentration is assessed. A flotation bank of two and three 5L Denver cells was implemented, and air flow was distributed down the bank as increasing and decreasing profiles. It was observed that when operating the bank configurations with a moderate frother concentration (10 ppm DF 400) the increasing profile provided the highest Cu enrichment ratio at the expense of a slight reduction in Cu recovery. This increase in selectivity was mainly due to a significant reduction in the water recovery and mass-pull in the first cell. When the bank operated with a high frother concentration, i.e., well beyond the CCC, a significant increase in water recovery was observed, producing a significant loss in selectivity that could not be compensated by air profiling. © (2023) Wroclaw University of Science and Technology.